2014
DOI: 10.2147/ijn.s64100
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of poly(lactic-co-glycolic acid)/poly(lactic-acid) microspheres through intravitreal injection in rabbits

Abstract: Poly(lactic-co-glycolic acid) (PLGA) and/or poly(lactic-acid) (PLA) microspheres are important drug delivery systems. This study investigated eye biocompatibility and safety of PLGA/PLA microspheres through intravitreal injection in rabbits. Normal New Zealand rabbits were randomly selected and received intravitreal administration of different doses (low, medium, or high) of PLGA/PLA microspheres and erythropoietin-loaded PLGA/PLA microspheres. The animals were clinically examined and sacrificed at 1, 2, 4, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…A reduced scotopic ERGs was also observed, suggesting photoreceptor dysfunction. On the contrary, low concentrations of PLGA MSs (intravitreal concentration 2 mg/mL) appear well tolerated and did not alter retinal function, findings consistent with previous studies describing the safety of low concentration intravitreal PLGA MSs in rabbit eyes A C C E P T E D M A N U S C R I P T [24,44]. In larger eyes with higher vitreous cavity, reduced inflammatory reaction is expected as observed with PLGA rods.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 1 more Smart Citation
“…A reduced scotopic ERGs was also observed, suggesting photoreceptor dysfunction. On the contrary, low concentrations of PLGA MSs (intravitreal concentration 2 mg/mL) appear well tolerated and did not alter retinal function, findings consistent with previous studies describing the safety of low concentration intravitreal PLGA MSs in rabbit eyes A C C E P T E D M A N U S C R I P T [24,44]. In larger eyes with higher vitreous cavity, reduced inflammatory reaction is expected as observed with PLGA rods.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…For preclinical development in animal models and for potential clinical development, we have chosen to prepare biodegradable microspheres (MSs) using poly-lactic-coglycolic acid (PLGA) to provide a controlled delivery of the drug in a long fashion. Particle size can be reduced to allow injection of a suspension through a regular 30G needle and provide the sustained release of active products [20][21][22].PLGA, approved by FDA and the European Medical Agency for intraocular use [23,24], is progressively hydrolysed in its monomers (lactic acid and glycolic acid), and subsequently converted into CO 2 and water via Kreb's cycle. Biodegradation in PLGA microspheres is described to occur in the polymeric matrix through a homogeneous hydrolytic chain cleavage mechanism leading to a sustained release of the active compounds included in the polymeric matrix [23,24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Examinations were performed by evaluating retinal histological and functional changes up to 12 weeks post administration. This study demonstrated that intravitreal injection of a PLGA/PLA microspheres drug delivery system resulted biocompatible and safe (Rong et al, 2014). In the present work a small amount of microspheres was used in an attempt to combine good tolerance at long term with the need of detectable…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…They indicated that no inflammation nor cell toxicity in the retinas was triggered by the microspheres, the degraded products, or the changed microenvironments in the eyes. Ocular tissues show great tolerability and biocompatibility after the intravitreal administration of PLGA material (Abrego et al, 2015;Giordano et al, 1995;Rong et al, 2014;Veloso et al, 1997). However, an initial foreign body response after intravitreal injection can occurs under normal physiological conditions with no damage to the retina (Giordano et al, 1995).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…IODDS based on biodegradable particulate carrier systems have been extensively investigated for the sustained release of therapies to address these problems. Poly(lactide-co-glycolide) acid (PLGA) is approved by the FDA and European Medical Agency for use in intraocular devices [17,21]. Among the different IODDS, microspheres (MSs) have recently gained considerable attention for ocular applications [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%